PENCAPAIAN TARGET KOMPETENSI MAHASISWA KEBIDANAN PADA MASA PANDEMI COVID-19 DI PRAKTEK BIDAN MANDIRI (PMB) DI WILAYAH KABUPATEN KEDIRI TAHUN 2021 - Endah Luqmanasari; Wahyu Nuraisya (STIKES dan AKZI Karya Husada Kediri, 2022)
Competence is a sufficient ability to do certain things in order to achieve what is expected, competence is also the knowledge and skills possessed by each individual that is applied in thinking and behaving where the individual will show actual quality in carrying out a task and work. This study aims to determine the achievement of the competency target of midwifery students during the COVID-19 pandemic in PMB, Kediri Regency. This type of research is quantitative with a retrospective research design. This research started from January to December 2021 at PMB in the Kediri Regency. The population in this study is the Independent Practice of Midwives with a sample of 30 places with a total sampling. The measuring instrument used is a questionnaire. A total of respondents (15%) have sufficient competence, while 28 respondents (85%) have good competence. It can be concluded that the achievement of competence in midwifery students during the Covid-19 pandemic was in the good category. There are three competencies whose achievement targets are lacking, namely midwifery care in childbirth, midwifery care for postpartum mothers and BBL, insertion and removal of implants and IUDs. The results of this study are expected that midwifery students can improve the assignment of competency achievement.